Ways to Increase the Share of Direct Taxes in the Formation of State Budget Revenues (Eurasian Scientific Herald, 2022)
This article provides a detailed analysis of the importance of local taxes in the state budget, national and global practice, their role in state budget revenues and forecasts of local tax revenues. It also researches the current state and tax rates on land and property taxes in various countries in Asia and Africa. In addition, property tax revenues in Europe have been studied in terms of developed and developing countries. Scientific conclusions and recommendations on the current situation with local taxes in our country are given by studying the importance of local taxes in the state budget, learning national and international practice